2015
DOI: 10.1002/pro.2790
|View full text |Cite
|
Sign up to set email alerts
|

Mutations can cause light chains to be too stable or too unstable to form amyloid fibrils

Abstract: Light chain (AL) amyloidosis is an incurable human disease, where the amyloid precursor is a misfolding-prone immunoglobulin light-chain. Here, we identify the role of somatic mutations in the structure, stability and in vitro fibril formation for an amyloidogenic AL-12 protein by restoring four nonconservative mutations to their germline (wild-type) sequence. The single restorative mutations do not affect significantly the native structure, the unfolding pathway, and the reversibility of the protein. However,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
59
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 35 publications
(68 citation statements)
references
References 42 publications
8
59
1
Order By: Relevance
“…More recent studies have painted a more differentiated picture. Mutations that alter the interface in AL-LC dimers may alter amyloid formation without altering V L monomer stability (44,62).…”
Section: Discussionmentioning
confidence: 99%
“…More recent studies have painted a more differentiated picture. Mutations that alter the interface in AL-LC dimers may alter amyloid formation without altering V L monomer stability (44,62).…”
Section: Discussionmentioning
confidence: 99%
“…27,28,36 y=A1A21+efalse(xx0false)/normaldnormalx+A2 where A 1 is the initial fluorescence value, A 2 is the final fluorescence value, x 0 is the midpoint (or t 50 value), and dx is defined as the time constant.…”
Section: Methodsmentioning
confidence: 99%
“…Our theoretical understanding of LC amyloidogenesis comes almost exclusively from in vitro studies of fibrillogenesis using recombinant VL fragments of κ4 [20, 3639], λ6 [21, 40, 41] and κ1[18, 19, 4244] LC subgroups produced in E. coli . Fibril formation from these components often requires harsh conditions such as low pH, agitation, or the presence of chaotropes, indicating the need for a denaturing milieu to initiate protein misfolding and, consequently, fibril formation.…”
Section: Discussionmentioning
confidence: 99%
“…Fibril formation from these components often requires harsh conditions such as low pH, agitation, or the presence of chaotropes, indicating the need for a denaturing milieu to initiate protein misfolding and, consequently, fibril formation. Although there are rare exceptions [19, 45], these studies demonstrated a general inverse correlation between VL folding free energy and the propensity for in vitro fibrillogenesis, such that less stably folded VL domains more readily form fibrils. Thus, de novo fibrillogenesis from soluble VL domains can be rapid and requires misfolding of the VL, allowing structured self-association into thermodynamically stable multimers that act as templates, or seeds, for the recruitment of additional VL domains.…”
Section: Discussionmentioning
confidence: 99%